Asuhan Kebidanan pada Balita dengan Baby Gym untuk Meningkatkan Kesehatan di Desa Mangunweni Kecamatan Ayah - Khulasoh; Eni Indrayani; Juni Sofiana (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Toddlers are a vulnerable age group to growth and developmental disorders; therefore, appropriate stimulation is needed to improve their health status. This community service activity aimed to improve toddlers’ health through midwifery care by implementing baby gym exercises. The methods used in this activity included health education, baby gym demonstrations, and direct practice assistance for mothers with toddlers. The targets of this activity were mothers and toddlers in Mangunweni Village, Ayah District. Evaluation was conducted through observation of maternal involvement, mothers’ ability to perform baby gym exercises, and toddlers’ responses before and after the intervention. The results showed an improvement in mothers’ knowledge and skills in independently performing baby gym exercises, as well as positive responses in toddlers, including increased physical activity, body flexibility, and comfort during stimulation. This activity also increased mothers’ awareness of the importance of early stimulation as part of midwifery care for toddlers. In conclusion, midwifery care for toddlers with the application of baby gym can be an effective effort to improve health and support toddlers’ growth and development.